(untitled) (Pedagogy of Higher and Secondary Education, 2011)
In article conditions of harmonization of the logic and emotional parties of process of preparation of the future teachers of art disciplines are aonsidered. Are analysed axemological conditions of this process, ways of formation of professional skill of the future teachers of music are certain.